Palladium-catalyzed aza-Wacker cyclization of O-homoallyl benzimidates: expeditious access to heteroatom-rich substituted 1, 3-oxazines via alkene trifunctionalization. Issue 24 (9th November 2022) - Zhang, Linlin; Qi, Lin; Du, Hui-Jie; Liu, Jia-Li; Cao, Tong-Yang; Yan, Zhi-Min; Li, Wei; Wang, Li-Jing
Abstract : A palladium-catalyzed aza-Wacker cyclization of O -homoallyl benzimidates was developed to afford a variety of 4-methylene-1, 3-oxazines, which are easily manipulated to give a family of heteroatom-rich functionalized molecules. Abstract : A palladium-catalyzed aza-Wacker cyclization of O -homoallyl benzimidates has been developed to afford a variety of useful 4-methylene-1, 3-oxazine building blocks in moderate to good yields. The synthetic utility of the 4-methylene-1, 3-oxazines is illustrated by the conversion of the exo CC bond to a diverse collection of heteroatom-rich moieties through subsequent electrophilic addition enabling C–I, C–Br, C–Cl, C–O, C–N, and C–C bond formations. These tandem protocols scale well, and their products are demonstrated to be valuable frameworks for use in medicinal and biological chemistry.